Investigation of polarization switching of VCSEL subject to intensity modulated and optical feedback. (December 2015) - Nazhan, Salam; Ghassemlooy, Z.; Busawon, K.; Gholami, A.
Abstract: This study presents the results of an experimental investigation of the polarization switching (PS) of vertical-cavity surface-emitting lasers (VCSELs) using the so-called polarization-rotated optical feedback mechanism. In particular, the experiments is performed by changing the laser driving current, optical feedback (OF) level, modulation signal parameters, such as frequency, modulation-depth in order to assess their influences on the PS of VCSEL. We show that a smaller polarization angle θ p is required to realize PS with increasing the level of OF. Moreover, for a fixed OF level and increased bias current a smaller θ p is required to ensure PS. However, for a fixed OF and variable modulation parameters, both the frequency and modulation-depth lead to the elimination of PS over the entire range of measurement. Highlights: We have considered the effects of modulation frequency and amplitude to Investigation of polarization switching (PS) properties under a range of bias current. We have shown that both modulation frequency and amplitude does lead to a significant change in PS properties, thus limiting effects of optical feedback on the polarization properties of VCSEL. The results show that there is no PS for modulation frequency =200 MHz. We also demonstrated that the bias current can affect the PS dynamic of VCSEL.